PENDEKATAN GIZI DAN EDUKASI SARAPAN UNTUK MENDUKUNG KONSENTRASI BELAJAR SISWA SD HUTADAME - Sihombing, S.Si, M.Si, Dewi Restuana; Daniela, Connie; Pandiangan, Maruba (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
The lack of breakfast habits among elementary school students is one factor that can reduce concentration levels during the learning process. At Huta Dame 2 Public Elementary School in Samosir Regency, most students arrive at school without breakfast, resulting in low focus and participation in learning activities. This community service activity aims to raise awareness of the importance of breakfast through educational outreach and direct intervention in the form of providing a healthy breakfast. The implementation method includes providing nutrition education materials to students and parents and providing a nutritious breakfast for three consecutive days to all students. In addition, observations and interviews with teachers were conducted to assess changes in student behavior and concentration in class. The results of the activity showed an increase in knowledge about the importance of breakfast, positive changes in students' breakfast habits, and reports from teachers regarding increased student attention and participation during learning. This activity demonstrates that an educational approach accompanied by direct practice can have a real impact on healthy behavior and support the learning process. Similar programs are recommended for continued implementation in schools with comparable conditions.